Exploring the nature of desire in Andre Aciman’s Call Me By Your Name: from page to screen by Luca Guadagnino - Akter, Shammy (Brac University, 2022)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Masters of Arts in Teaching to Speakers of Other Languages, 2022.